2017
DOI: 10.3233/cbm-160175
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of LRP6 gene expression in tumoral tissues of colorectal cancer

Abstract: Due to the profound overexpression of LRP6 in sporadic and rectal types of cancer compared to normal colonic ones, antagonist related approaches can be promising for targeted therapies of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Moreover, LRP6 activates the Wnt/β-catenin pathway, promoting the genesis and development of tumors (36,37). LRP6 is expressed at high levels in CRC (38) and is involved in the regulation of its malignant development in vitro and in vivo (23,39). In the present, it was demonstrated that miR-629 directly targeted LRP6 and suppressed the Wnt/β-catenin pathway, thereby controlling proliferation, apoptosis, migration, and invasion of CRC cells in vitro and tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, LRP6 activates the Wnt/β-catenin pathway, promoting the genesis and development of tumors (36,37). LRP6 is expressed at high levels in CRC (38) and is involved in the regulation of its malignant development in vitro and in vivo (23,39). In the present, it was demonstrated that miR-629 directly targeted LRP6 and suppressed the Wnt/β-catenin pathway, thereby controlling proliferation, apoptosis, migration, and invasion of CRC cells in vitro and tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…Besides that, in a systematic review of 11 publications, using sequence data from 863 familial CRC cases and 1604 individuals without CRC, Broderick et al (2017) found no significant enrichment of LRP6 mutations in CRC [61,62]. Nevertheless, LRP6 is overexpressed in many CRC cell lines in comparison to normal epithelial cells, and 61% of malignant tissues isolated from sporadic CRC patients harbor higher LRP6 levels (Table 1) [53]. This increased LRP6 expression in CRC may result from hypermethylation of the Necdin promoter—a transcriptional repressor of the LRP6 gene [63].…”
Section: Lrp6 and Carcinoma Developmentmentioning
confidence: 99%
“…Mutations in genes associated with the Wnt/β‐catenin pathway result in functionally abnormal proteins with altered protein structures and protein interactions. The LRP6 gene encodes a transmembrane cell‐surface protein that is a major component of the Wnt receptor complex in the Wnt/β‐catenin signalling cascade 25 . LRP6 contains a large extracellular domain that binds to Wnt proteins.…”
Section: Discussionmentioning
confidence: 99%